2020
DOI: 10.3389/fpsyg.2020.00815
|View full text |Cite
|
Sign up to set email alerts
|

Farewell to Bright-Line: A Guide to Reporting Quantitative Results Without the S-Word

Abstract: Recent calls to end the practice of categorizing findings based on statistical significance have focused on what not to do. Practitioners who subscribe to the conceptual basis behind these calls may be unaccustomed to presenting results in the nuanced and integrative manner that has been recommended as an alternative. This alternative is often presented as a vague proposal. Here, we provide practical guidance and examples for adopting a research evaluation posture and communication style that operates without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
(36 reference statements)
0
7
1
Order By: Relevance
“…The pattern for stimulant-related diagnosis was not as well resolved in this study (Cummins & Marks, 2020;Kraemer, 2019). This is not consistent with the relationship between stimulant use and SMM observed in previous research, which identified an increased risk of SMM and maternal mortality after delivery (Hser et al, 2012;Jarlenski et al, 2020;Wolfe et al, 2005).…”
Section: Discussion Principal Findingscontrasting
confidence: 95%
“…The pattern for stimulant-related diagnosis was not as well resolved in this study (Cummins & Marks, 2020;Kraemer, 2019). This is not consistent with the relationship between stimulant use and SMM observed in previous research, which identified an increased risk of SMM and maternal mortality after delivery (Hser et al, 2012;Jarlenski et al, 2020;Wolfe et al, 2005).…”
Section: Discussion Principal Findingscontrasting
confidence: 95%
“…Binary logistic regressions were utilized to model each outcome variable using stepwise backward elimination to obtain a parsimonious model with predictive ability; all variables significant at the bivariate level were entered into the model, followed by the removal of the variable or set of dummy variables with the highest p -value in each progressive model. Models in which all variables, or at least one variable within a set of dummy variables, were significant at cutoffs of p < 0.10 and p < 0.05 [ 24 , 26 , 27 ] were presented given the potential for meaningfulness. Reporting of variables for such models follows the format: (Model 2; Model 3).…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with emerging statistical recommendations in the field calling for an end to reliance on bright-line significance testing, [30][31][32] we opt to report study findings by applying the postsignificance communication structure (POCS). 33 Instead of relying on null hypothesis significance testing to evaluate study findings, through POCS we make an evaluation of point estimates, CIs and corresponding p values in relation to the underlying scientific questions to make study conclusions. 33 As such, we consider p values as continuous rather than dichotomous variables and refrain from denoting significance based on a bright-line value, α.…”
Section: Results Evaluation Frameworkmentioning
confidence: 99%
“… 33 Instead of relying on null hypothesis significance testing to evaluate study findings, through POCS we make an evaluation of point estimates, CIs and corresponding p values in relation to the underlying scientific questions to make study conclusions. 33 As such, we consider p values as continuous rather than dichotomous variables and refrain from denoting significance based on a bright-line value, α.…”
Section: Methodsmentioning
confidence: 99%